The role of mentoring in public health nutrition workforce development. Perspectives of advanced-level practitioners - Palermo, Claire; McCall, Louise (Public health nutrition, 2008)
To explore the nature, role and utility of mentoring in the development of competence in advanced-level Australian public health nutritionists. Qualitative study using in-depth interviews. Eighteen advanced-level public health nutritionists working in academic and practice settings in Australia. The attributes and career pathways of the subjects were consistent with previous findings. Dissatisfaction with clinical practice was a key reason for choosing a career in public health. Experiential learning, postgraduate education and mentoring from both peers and senior colleagues were the most significant contributors to competency development. The subjects supported mentoring as an important strategy for public health nutrition workforce development and articulated the characteristics and models important for mentoring relationships in public health nutrition. The present study suggests mentoring was an important part of competency development for advanced-level public health and community nutritionists in Australia. Mentoring programmes based on experiential learning may assist in developing public health nutrition workforce competence.